Pendidikan Keluarga Berbasis Gender: Sebuah Studi Pustaka - Mulyono, Mulyono; Maktumah, Luluk (CV. Creative Tugu Pena, 2023)
Gender bias that exists in the family or society at large will have a huge psychological impact on children in their future lives. The aim of this research is to describe Gender-Based Family Education. Researchers use library research by collecting data from credible reference sources in several reputable national and international journals. The results of this finding are that the success of education in the family must be supported by a conducive atmosphere from the family or parents themselves, as well as the child's environment and social friends. In gender education, parents have a very important role in educating and directing their children, because if gender bias occurs in a family, this will greatly influence the children's mindset in the future. Keywords: Gender-Based Family Education, Gender Education, Gender Family Education